IMPLEMENTASI AKAD MUDHARABAH PADA PRODUK TABUNGAN KOPERASI SYARIAH (Studi Kasus Pada Kspps Nuri Jatim Cabang Sokobanah II Sampang) - Fendi; Amin; Abdul Bari (Ekosiana Jurnal Ekonomi Syari ah, 2021)
Abstract: Mudharabah agreement is an agreement between two parties where the bank acts as the manager and custumer as the capital owner, the profit obtained will e shared according tho the agreement, if there is a loss, it will e fully borne by the owner of the capital, the manager only bears the loss of the business and and work only. this study ains to determine how the application of the mudharabah contract to the savings product in KSSPPS NURI JATIM and whether the application of the mudharabah contract to the saving products is in accordance with sharia.With this study, the author will provide an overview of the implementation of the mudharabah contract on savings products and see what is in theory with those apllied in banks, this study uses qualitative methods, namely a method by analyzing the results of research that produces descriptive analysis data. In addition, data collection was carried out by direct interviews at KSPPS NURI JATIM CAB.SOKOBANAH II, NURI JATIM Customer and Islamic Economics Academics. The result of the study are savings products at NURI JATIM using the mudharabah mutlaqah contract, with a profit ratio of 25:75 (25 for customer and 75 for bank). The application of mudharabah contract apllied at NURI JATIM can be seen from the aspect of profit ratio in accordance sharia, because the ratio from the beginning has been determined by the bank. Seen from the aspect of the type of business applied, it is in accordance with sharia, where the NURI JATIM distribution of funds channeled to financing.   Keyword: Implemetation, mudharabah contract, and sharia concept     DAFTAR PUSTAKA Antonio, Syafi’i,  Bank Syariah dari Teori ke Praktek, Jakarta: Gema Insani, 2001. Basyir, Azhar , Negara dan Pemerintahan dalam Islam, Yogyakarta: UII Press, 2000 Dahlan, Irmayanti, dan Lilies Handayani. “Analisis Penerapan Bagi Hasil Akad Mudharabah Dan Akad Musyarakah Pada Bank BRI Syariah Kota Makassar.” El-Iqtishod: Jurnal Ekonomi Syariah 4, no. 1 (10 November 2020): 34–45. Ismail, Perbankan Syariah, (Jakarta: Kencana Ilmu, 2015 Karim, Adiwarman A, Bank Islam Analisis Fiqih dan Keuangan, Jakarta: PT. Raja Grafindo Persada, 2010 Kasmir, Bank dan Lembaga Keuangan Lainnya, Jakarta: Rajawali Pers,2009 Khunaifi, Aang. “Aktualisasi Pemasaran Syariah.” MIYAH : Jurnal Studi Islam 12, no. 1 (26 Februari 2017): 52–71. Kunaifi, Aang. “IMPLEMENTASI STRATEGI PEMASARAN BERBASIS HUMAN SPIRIT DALAM MARKETING 3.0 DI BANK PEMBIAYAAN RAKYAT SYARI’AH (BPRS) BHAKTI SUMEKAR KABUPATEN SUMENEP.” Masters, UIN Sunan Ampel Surabaya, 2015. http://digilib.uinsby.ac.id/4472/. ———. Manajemen Pemasaran Syari’ah Pendekatan Human Spirit: Konsep. Etika, Strategi dan Implementasi. Yogyakarta: Maghza Pustaka, 2016. ———. “OPTIMALISASI LABORATORIUM KEUANGAN SYARI’AH DALAM MENINGKATKAN LITERASI SIVITAS AKADEMIKA TERHADAP PRODUK IKNB SYARI’AH.” CENDEKIA: Jurnal Studi Keislaman 2, no. 2 (2016): 221–39. https://doi.org/10.37348/cendekia.v2i2.27. Kunaifi, Aang, dan Lailatul Qomariyah. “Developing Company Images Through Spiritual Public Relations Facing Covid-19 Outbreak.” Jurnal Iqtisaduna 1, no. 1 (10 September 2021): 13–22. https://doi.org/10.24252/iqtisaduna.v1i1.15808. Kunaifi, Aang, Fadali Rahman, dan Risca Dwiaryanti. “The Philosophy and Authentication of Welfare Equalization in the Islamic Economy.” Jurnal Kajian Peradaban Islam 4, no. 2 (24 Juni 2021): 54–62. https://doi.org/10.47076/jkpis.v4i2.67. Millah, Hayatul. “Implementasi Nisbah Bagi Hasil Produk Tabungan Mabrur Melalui Akad Mudharabah Mutlaqah Dalam Perspektif Ekonomi Islam :” Iqtishodiyah : Jurnal Ekonomi Dan Bisnis Islam 7, no. 1 (13 Februari 2021): 91–103. https://doi.org/10.36835/iqtishodiyah.v7i1.492. Misbahuddin, Herman. “Sistem Akad Mudharabah dalam Perekonomian Islam.” TAFAQQUH: Jurnal Hukum Ekonomi Syariah Dan Ahwal Syahsiyah 6, no. 1 (30 Juni 2021): 1–14. Nandaningsih, Nadia, dan Yuli Dwi Yusrani Anugrah. “Konsep Pembiayaan Mudharabah Dalam Perbankan Syariah.” Muhasabatuna : Jurnal Akuntansi Syariah 3, no. 1 (1 Juni 2021): 61–66. Ruslizar, Pengaruh Tingkat Bagi Hasil Deposito Mudharabah, Financing, To Deposito Ratio, dan Suku Bunga Deposito Terhadap Pertumbuhan Deposito Mudharabah Pada Bank Umum Syariah di Indonesia. Jurnal Ilmiah Ekonomi Akuntansi (JIMEKA). Vol.1 No 2, 2016 Saputra, Taufik Aris, Aang Kunaifi, dan Siti Azizah. “DIVERSIFIKASI PRODUK PENDEKATAN ISLAMIC ETHIC DALAM MENINGKATKAN OMSET BISNIS RETAIL.” CENDEKIA: Jurnal Studi Keislaman 7, no. 1 (9 Juli 2021): 1–16. Shabri, Pengaruh Prinsip Bagi Hasil, Tingkat Pendapatan, Religiusitas dan Kualitas Pelayanan Terhadap Keputusan Menabung Nasabah Pada Bank Syariah Di Banda Aceh. Jurnal Megister Akuntansi Pancasarjana Universitas Syiah Kuala. Vol.6 No.3, 2015 Suazhari, Pengaruh Pemahaman Manajer Tentang Standar Akuntansi Keuangan Syariah dan Peran Dewan Pengawas Syariah Terhadap Laporan Keuangan. Jurnal Perspektif Ekonomi Darussalam. Vol. 1 No, 2, 2015 Yaya, Akuntansi Perbankan Syariah Teori dan Praktik Kontemporer Berdasarkan PAPSI 2013, (Jakarta: Salemba Empat,2016 Yulisnawati, Yulisnawati. “IMPLEMENTASI SIMPANAN AKAD MUDHARABAH DI KOPERASI SERBA USAHA BAITUL MAAL WATTAMWIL RAHMAT SYARIAH SEMEN KEDIRI PERSPEKTIF FATWA DEWAN SYARIAH NASIONAL MAJLIS ULAMA INDONESIA.” Bertuah: Journal of Sharia and Islamic Economics 1, no. 1 (16 Desember 2020). https://ejournal.kampusmelayu.ac.id/index.php/ Bertuah/article/ view/156.